An a priori estimator for the delay distribution in global hybrid multicast - Matthias Wählisch and Thomas C. Schmidt (Association for Computing Machinery (ACM), 2009)
Hybrid multicast is regarded a promising technology to overcome the inter-domain deployment problem for group communication. Realistic performance estimators are difficult to obtain due to the diversity of overlay concepts and their complex dependence on the global Internet topology that withstands straightforward simulations or measurements. We contribute a simple analytic model for the expected delay distribution. Parametrized by realistic measurement values, this should serve as a first order estimator for quantifying the delay penalties in a global-scale hybrid multicast packet distribution. We diagnose a strong dependence on hop counts and proximity awareness for the overlay multicast approach in use with promising results for most efficient schemes.
Keywords: Analytical model; IP multicast; structured overlay networks; inter-domain; Scribe; CAN